Standardization of the morphogenetic periods of the cardiogenesis of Wistar rat (Rattus norvegicus) - Ramírez-Soto, Natalya (2021)
Aim: To describe the morphogenetic cardiogenesis processes of the Wistar rat (Rattus norvegicus) in a vivarium located in Cali (Colombia). Materials and methods: observational-descriptive study of cross-section where the four morphogenetic processes of the heart development (cardiogenic field, cardiac tube, cardiac loop and septum and compartmentalization) were described, through histochemical preparations in hematoxylin-eosin, of 76 embryos obtained from 22 females (one for each gestation day) from the ninth day of intrauterine development. Results: A comparative approximation was carried out between the gestational stages of the Wistar rat in days, and the weeks of heart development in humans, being 3 and 9 for the cardiogenic field, 4 and 11 for the cardiac tube, 4 and 12 for the cardiac loop and 5 and 13 for the septum and compartmentalization respectively, with a few variations due to reported literature. Conclusions: Identifying the morphogenetic processes of the cardiogenesis of the Wistar rat (Rattus norvegicus) in a vivarium located in Cali will allow the establishment of a space-time based line for the comparative embryonic study of the human heart development. The standardization of the four cardiogenetic periods in a Wistar rat biomodel enables the investigators to perform studies about the etiopathogenesis of congenital cardiac anomalies through comparative embryology. The identification of the gestational age where the morphogenetic processes take place contributes to diminish the unnecessary deaths of Wistar rat biomodels in future studies.